Distributed data validation and reconstruction for water distribution monitoring systems - Ortiz, Gregorio L. III (College of Engineering, University of the Philippines Diliman, 2017)
Water distribution monitoring systems are critical components in proper operation of water utilities. However, such systems often suffer from the presence of erroneous measurements. There exists centralized methods for dealing with these errors, but they are inadequate due to their reliance on the GSM/GPRS network, making them unreliable and unsuitable for real-time applications. A distributed data validation and reconstruction approach is presented that utilizes energy and mass balance relations in order to correct erroneous data. This method was found to reduce error within the network by using complementary performance of energy and mass balance operations.